If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7x + -9x + 10 = 0 Reorder the terms: 10 + 3x + 7x + -9x = 0 Combine like terms: 3x + 7x = 10x 10 + 10x + -9x = 0 Combine like terms: 10x + -9x = 1x 10 + 1x = 0 Solving 10 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 0 + -10 1x = 0 + -10 Combine like terms: 0 + -10 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 6r^2-6d^2=0 | | y+.7-4.5=2.3(y-3) | | 10-(1/3)x | | 5x+6=24+2x | | x-0.5x-0.5x-0.25x=12 | | 5(a-4)=35 | | (13x+9)=(5x+9) | | -6x-5=-9 | | (5x+5)=(115) | | x-6.0=26.0 | | 7y+9=8y+1 | | 2x^4-5x=2 | | 5x+29.0=54.0 | | 2y-71.0=25.0 | | 1/3x^3-4x-11/3 | | 4w+5=3w+9 | | loge(42)=2x+1 | | 6y=-2-x | | (x*40)+(1.5x*5)=576 | | 69*200000/X=17.92 | | 5/7m35 | | -8(s+2)=28 | | x*40+1.5*x*5=30000 | | 9w=10w-4 | | 2y-63.0=10.0 | | 2b-7/3=3/3 | | x-2.0=27.0 | | -8x+6-12=-30 | | 6x+21=x+7 | | 12+4x-x=x+28 | | 5x+28.0=58.0 | | 2b-31/3=11/3 |